2021
DOI: 10.1111/apa.15824
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation of the preterm infant in the delivery room using nasal high flow: A 5—year retrospective analysis

Abstract: Aim This study reviews clinical outcomes after initiating a routine policy of preterm respiratory stabilisation using nasal high flow (HF) in the delivery room (DR). Method This was a retrospective observational cohort study in a single‐centre neonatal intensive care unit and included all neonates born before 32 weeks of gestation between 1 April 2015 and 31 March 2020. Stabilisation measures and outcomes were recorded including oxygen requirements, admission temperature, surfactant administration, invasive ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Neonatologists have applied nHFT after extubation, 72,73 as primary mode for treating respiratory distress, 56,72,74 preventing apnea of prematurity, 75 weaning from other support modes 76 and even as a tool for respiratory stabilization in the delivery room, 77 to support endotracheal intubation, 78 during transport 79 and in nontertiary centers 80 . However, only a few trials included a small number of infants <28 weeks' gestation 73,81,82 .…”
Section: Noninvasive Respiratory Support In the Nicusmentioning
confidence: 99%
“…Neonatologists have applied nHFT after extubation, 72,73 as primary mode for treating respiratory distress, 56,72,74 preventing apnea of prematurity, 75 weaning from other support modes 76 and even as a tool for respiratory stabilization in the delivery room, 77 to support endotracheal intubation, 78 during transport 79 and in nontertiary centers 80 . However, only a few trials included a small number of infants <28 weeks' gestation 73,81,82 .…”
Section: Noninvasive Respiratory Support In the Nicusmentioning
confidence: 99%
“…Furthermore, it found that 59% of very preterm infants (n = 292) were stable under HFNC, and HFNC stabilization rates were higher in this group (gestational age of 27−32 weeks) compared with extremely preterm infants (63% vs. 53%, p = 0.036). 99 Therefore, the risk of HFNC therapy for extremely preterm infants was supposed to be higher.…”
Section: ≥28 Weeks (2d)mentioning
confidence: 99%
“…For extremely preterm infants, there may be risks in the use of HFNC in the delivery room after birth. 99 Therefore, it is recommended that preterm infants born at ≥28 weeks of gestation can use HFNC for delivery room stabilization and transfer.…”
Section: ≥28 Weeks (2d)mentioning
confidence: 99%
See 2 more Smart Citations